2017
DOI: 10.1016/j.jclepro.2016.09.143
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dark fermentative hydrogen and ethanol production from waste bread in a mixed packed tank reactor

Abstract: Simultaneous dark fermentative hydrogen and ethanol production from waste bread in a mixed packed tank reactor (MPTR) was investigated. Waste bread was first hydrolyzed by the produced enzymes to generate the waste bread hydrolysate which was subsequently introduced to the MPTR for dark fermentative hydrogen and ethanol production. The optimal hydrogen and ethanol production rates were 15.01 mmol/(h•L) and 23.25 mmol/(h•L) when the organic loading rate reached 32 g/(L•d). The unit hydrogen and ethanol producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 12 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…The FCE include equipment purchase cost, process piping, equipment installation, electrical systems, instrumentation and controls, yard improvements, buildings, and construction as well as the working capital cost (WCC) which might represent 6.5% of FCE as suggested by Han et al [52]. Therefore, the FCE for design a treatment plant with 1000 m 3 /day of capacity reach to USD 950,000.00.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FCE include equipment purchase cost, process piping, equipment installation, electrical systems, instrumentation and controls, yard improvements, buildings, and construction as well as the working capital cost (WCC) which might represent 6.5% of FCE as suggested by Han et al [52]. Therefore, the FCE for design a treatment plant with 1000 m 3 /day of capacity reach to USD 950,000.00.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the FCE for design a treatment plant with 1000 m 3 /day of capacity reach to USD 950,000.00. (Table 3) The additional costs for the treatment process might reach 50% of the equipment cost which was equivalent to USD 475,000.00 [52]. The TCI of the plant could reach to USD 1,425,000.00.…”
Section: Resultsmentioning
confidence: 99%
“…e method mentioned by Han et al [10] was used to quantify protease activity with modification. Exactly, the reaction mixture containing 0.3 mL of 20% (w/v) azocasein (Sigma), 0.1 mL of enzyme preparation, and 0.2 mL of citrate buffer at pH 5.2 was incubated for 4 h at 45°C.…”
Section: Protease Assaymentioning
confidence: 99%
“…BW is a good fermentation feedstock also since it is available year round and its availability is not associated with the harvest season [9]. It is used for its high yielding bioenergy substrates mainly for ethanol and biohydrogen production [10]. e work of Pleissner et al [11] suggested hydrolysed BW for bioplastic production by Halomonas boliviensis.…”
Section: Introductionmentioning
confidence: 99%
“…The specific cost of these products (kg/U.S.D) is the deliberated, which is dependent on the utility cost , annual costs of capital , raw material cost , extra cost , and the annual PhACs production, as presented by [ 36 ] (Equation (6)). …”
Section: Resultsmentioning
confidence: 99%